THE MAIN NOTIONS OF PHRASEOLOGY - Yo’ldasheva Asal,; Igamberdieva Shahnoza, (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
This article provides information about the basic concept, role, types and classification of phraseological units. Some classifications have been given as an example by several scientists, provides information about the linguistic and cultural and linguodidactic features of the use of phraseological units in the educational process. There are also some researchers who have paid great attention to approaches to teaching phraseological units.